DOES ATTENTION MEDIATE THE RELATIONSHIP BETWEEN CHRONIC PAIN AND FALLS IN OLDER ADULTS?. (11th November 2018) - Leveille, S; Hausdorff, J; Dong, Z; Milberg, W; McLean, R; van der Leeuw, G
Abstract: Accumulating evidence points to an increased fall risk among older adults who have persistent multisite pain. A better understanding of this pain hazard could lead to new interventions to reduce fall risk in older adults. The MOBILIZE Boston Study II included a battery of tests to assess the attentional domain, as well as the problem of persistent multisite pain. The 354 participants completed monthly fall calendars during the subsequent 2 years. Incidence rate ratios for falls were derived from multivariable negative binomial models, adjusted for fall risk factors. We found that elders who had multisite pain had a 51% increase in fall risk (adj. IRR=1.51, 95% CI: 1.51–2.10). Several measures of attention mediated the pain-falls relationship including measures of selective attention, visual attention and attentional switching. Studies are needed to determine whether interventions that incorporate attentional challenges could reduce fall risk in older adults who have multisite pain.